Procedure of credit rating: a study on WASO credit rating Company (BD) Ltd. - Badhan, Naimul Rashid (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.